Teologiczna symbolika wybranych postaci historii Izraela w mowie Matatiasza (1 Mch 2,51-61) - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2015)
The core of Mattathias’ deathbed speech addressed to his sons and all the participants of the Maccabaean rising (1 Macc 2:51-61) is the command to be faithful to the law and the covenant as a foundation of patriotism as it was then understood – love of one’s homeland and defense of traditions that constituted the identity of the people who inhabited it. The biblical author recalls the major figures in the history of Israel to show the struggle of the insurgents as a continuation of the history created by the heroes of the past. The object of the article is to present the theology of those particular figures from the history of Israel in the context of the then ongoing events whereby they became models to follow and a source of perseverance in the undertaken struggle against the pagan invaders from the Seleucid empire.